Perbandingan Metode Proporsi dengan Metode Resazurin Microtiter Assay (Rema) untuk Deteksi Mycobacterium tuberculosis yang Resisten Terhadap Rifampisin - Yenti Purnamasari; Sartini Sartini; Faisal Attamimi; Muh. Nasrum Massi (Halu Oleo University, 2015)
Tuberculosis (TB) is one of the high infectious diseases in Indonesia caused by Mycobacteriumtuberculosis. Drugs which used for tuberculosis therapy has been widely reported experiencing resistance, while inappropriately treatment will lead to not effective and efficient care. Culture in Lowenstein Jensen medium is a gold standard to perform the drug susceptibility but it takes a long time to get results, therefore, new methods were developed to replace it, one of them is colorimetric method. This research aimed to compare Rifampicin susceptibility test in colorimetric method use REMA and culture method use Lowenstein Jensen medium. This study was a cross sectional with experimental laboratory design used 42 sputums from patients with tuberculosis, done at October 2010 until March 2011. In this research, 5 samples rifampicin resistant have been detected. As a results, we founded Rifampicin susceptibility test of REMA have 80 % sensitivity, 100 % specificity, 100 % PPV, and 97 % NPV when compared with culture method.Keywords:Proportion, Resazurin, Mycobacterium tuberculosis, Resistance